PP038 EQ-5D-3L Electronic Version Development For The Brazilian Population. (2017) - Miguel, Sandro; Bagattini, Ângela; Camey, Suzi; Polanczyk, Carisi; Cruz, Luciane
Abstract : INTRODUCTION: Quality of Life (QoL) is considered to be an important outcome which is widely used in Health Technology Assessment (HTA). In economic evaluations QoL is represented by quality-adjusted life years (QALYs) - adding utility scores to the years of life lived in a determined health status (1). The EuroQol - 5 dimensions (EQ-5D) is a QoL questionnaire that generates utility scores and provides a simple and generic measure of health (2). Electronic QoL instruments have been reported equivalent to paper-based methods, however no studies have assessed agreement between EQ-5D application methods in Brazil (3). Thus, our study aimed to evaluate the measurement equivalence between the original (paper) and adapted (tablet) versions of the EQ-5D-3L Brazilian questionnaire. METHODS: A cross-sectional study was conducted on 509 adult individuals selected at random in economically different regions of two major Brazilian cities. EQ-5D-3L and Visual Analogue Scale, paper and tablet versions, were applied. Subjects were randomized to two groups; one group assigned for test-retest assessment using only electronic media (tablet-tablet), and a crossover group - half of which answered the tablet version before the paper questionnaire (tablet-paper), and the other half which answered the tablet version after the paper questionnaire (paper-tablet). There was a washout period of a minimum of 24 hours and maximum of 7 days between applications. The Intraclass Correlation Coefficient (ICC) and kappa coefficient were used to determine the agreement between methods. The level of significance was set at .05 for all analyses. RESULTS: Females predominated in all groups, and the mean age ranged from 41 to 44 years. In the crossover group the obtained ICC values were: .76 (CI .58–.89) for EQ-5D scores and .77 (CI .68–.84) for Visual Analogue Scale (VAS) scores in the tablet-paper subjects; .83 (CI .75–.89) for EQ-5D scores and .75 (CI .67–.85) for VAS scores in the paper-tablet subjects. In the test-retest group, the ICC values were .85 (CI .73–.91) for EQ-5D scores, .79 (CI .66–.87) for VAS scores. Kappa values were higher than .69 in test-retest group. Internal consistency was similar between methods. CONCLUSIONS: Paper and tablet versions of the EQ-5D were equivalent. Test-retest and crossover agreement was high and the acceptability of the methods was similar.